Central odontogenic fibroma: Report of case with immunohistochemical study - Savas Iordanidis; Athanasios Poulopoulos; Apostolos Epivatianos; Lambros Zouloumis (Wolters Kluwer Medknow Publications, 2013)
Objectives: To report a case of central odontogenic fibroma (COF) with immunohistochemical study. Clinical Presentation: We describe a case of epithelium-rich type of COF in the posterior region of the mandible of a 39-year-old woman. Immunohistochemical examination showed the odontogenic epithelium to be positive for high-molecular-weight cytokeratins, vimentin and CD99, and negative for CAM5.2. The stroma contained some myofibroblasts and many fibroblast-like cells positive for CD99. Conclusion: Our immunohistochemical findings, and especially the positive expression of vimentin from the epithelial cells of COF suggests that these cells are primordial. Last but not least, the presence of a relative small number of myofibroblasts in the stroma justifies the non-aggressive behavior of the neoplasm and supports that a part of stromal collagen of COF is produced by these cells.